2000
DOI: 10.1073/pnas.220409497
|View full text |Cite
|
Sign up to set email alerts
|

A metabolic defect promotes obesity in mice lacking melanocortin-4 receptors

Abstract: Core body temperature of Mc4r-null mice was normal, and they responded normally to cold exposure. Young nonobese Mc4r-null females were unable to induce uncoupling protein 1 (UCP1) in brown adipose tissue in response to peripheral leptin administration, whereas UCP1 mRNA was increased by 60% in the WT females. These results indicate that Mc4r deficiency enhances caloric efficiency, similar to that seen in the agouti obesity syndrome and in melanocortin-3 receptor-null mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
209
3
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 334 publications
(242 citation statements)
references
References 37 publications
22
209
3
3
Order By: Relevance
“…The present data give further support to the notion that the MC4 receptor is not only involved in a satiety response but also mediates an important influence on the metabolic status of the animals. A recent study shows that MC4 receptor-null mice have enhanced caloric efficiency (Ste Marie et al 2000), similar to that seen in the agouti obesity syndrome and in MC3 receptor-null mice (Butler et al 2000, Chen et al 2000. It is thus likely that both the MC3 and MC4 receptors are involved in the long-term effects that were observed on the food conversion ratio in this study.…”
Section: Discussionsupporting
confidence: 80%
“…The present data give further support to the notion that the MC4 receptor is not only involved in a satiety response but also mediates an important influence on the metabolic status of the animals. A recent study shows that MC4 receptor-null mice have enhanced caloric efficiency (Ste Marie et al 2000), similar to that seen in the agouti obesity syndrome and in MC3 receptor-null mice (Butler et al 2000, Chen et al 2000. It is thus likely that both the MC3 and MC4 receptors are involved in the long-term effects that were observed on the food conversion ratio in this study.…”
Section: Discussionsupporting
confidence: 80%
“…Thus the phenotypic feature of a deficit in energy expenditure that we have previously described in Pomc Ϫ/Ϫ mice (8) appears to be as a result of melanocortin deficiency rather than secondary to glucocorticoid insufficiency. This is in keeping with the phenotype of Mc4R Ϫ/Ϫ mice, another wellcharacterized model of melanocortin dysfunction, which are corticosterone replete but still consume 20% less oxygen then wild-type mice (30).…”
Section: Ap Coll and Associatessupporting
confidence: 76%
“…The data suggested that MC4R deficiency may enhance the metabolic efficiency. 14 In a pharmacological study, Adage et al 46 performed a PF study to evaluate the food intake-independent mechanisms of the melanocortin system in the development of obesity. Administration of the melanocortin receptor antagonist SHU9119 to rats reduced spontaneous locomotor activity and body temperature.…”
Section: Discussionmentioning
confidence: 99%
“…14 Ste Marie et al 14 found that the locomotor activity of young male nonobese MC4R knockout mice was significantly lower than that of wild-type mice. When normal mice were switched from a low-fat to a moderate-fat diet, they responded with an increased activity.…”
Section: Introductionmentioning
confidence: 99%